Safety and efficacy of guselkumab in Japanese patients with moderate‐to‐severe plaque psoriasis: a randomized, placebo‐controlled, ascending‐dose study. (1st March 2018) - Nemoto, O.; Hirose, K.; Shibata, S.; Li, K.; Kubo, H.
Summary: Background: The interleukin (IL)‐23/IL‐17 pathway is central in the pathogenesis of psoriasis. The favourable efficacy and safety of guselkumab, an IL‐23‐specific monoclonal antibody, has been demonstrated in global phase III studies of plaque psoriasis. Objectives: To evaluate the safety, efficacy and pharmacokinetics of single‐dose subcutaneous guselkumab in Japanese patients with moderate‐to‐severe plaque psoriasis. Methods: Patients with ≥ 10% of total body surface area involvement and a Psoriasis Area and Severity Index (PASI) ≥ 12 were randomized (5 : 1) to receive guselkumab or placebo in four cohorts of this double‐blind, placebo‐controlled, single ascending‐dose, single‐centre study. Safety, pharmacokinetics and clinical response were monitored at baseline and specific time points over a 24‐week follow‐up period. Results: To week 24, 55% (11/20) of patients in the guselkumab group and 50% (2/4) in the placebo group experienced ≥1 adverse event (AE). No deaths, serious AEs or AEs leading to treatment discontinuation were reported. Maximum clinical response was seen at week 16 with PASI 75 (≥ 75% improvement from baseline PASI) response in two of five (10 mg), four of five (30 mg and 300 mg) and three of five (100 mg) patients; and PASI 90 (≥ 90% improvement from baseline PASI) in zero of five (10 mg), three of five (30 mg), two of five (100 mg) and three of five (300 mg) patients. Mean maximum serum concentration (Cmax ) and area under the curve from time zero to infinity values increased in a dose‐proportional manner with a mean terminal half‐life of 15·6–17·6 days and median time to reach Cmax of 4–6 days. Conclusions: Guselkumab was generally well‐tolerated and exhibited sustained high levels of clinical response in Japanese patients with moderate‐to‐severe psoriasis.